Meconium-Stained Amniotic Fluid and Its Perinatal Feto-maternal Outcome (Community Based Medical Journal, 2022)
Meconium Stained Amniotic Fluid is associated with increased risk of operative delivery or caesarean section and increased rate of neonatal resuscitation, morbidity and mortality. A hospital-based prospective, observational study was conducted in the Obstetrics & Gynecology Department, NICU and Neonatal Ward of Naval Base Hospital, a tertiary care hospital of Bangladesh Navy, Chattogram, Bangladesh, between January 2020 and December 2021. A semi-structured questionnaire was prepared for both case and control group. 182 cases were enrolled as case and another 182 cases were as control. Antenatal checkup was significantly less in cases (p